Sex Differences in the Incidence and Risk Factors of Myocardial Injury in COVID-19 Patients: A Retrospective Cohort Study - Cheng, Ran; Liu, Chuan; Yang, Jie; Yang, Yuanqi; Chen, Renzheng; Ding, Xiaohan; Gao, Xubin; Ke, Jingbin; Yuan, Fangzhengyuan; He, Chunyan; Shen, Yang; Zhang, Limin; et al. (Frontiers in Physiology, 2021)
Male novel coronavirus disease (COVID-19) patients tend to have poorer clinical outcomes than female patients, while the myocardial injury is strongly associated with COVID-19-related adverse events. Owing to a lack of corresponding data, we aimed to investigate the sex differences in the incidence of myocardial injury in COVID-19 patients and to identify the potential underlying mechanisms, which may partly account for the sex bias in the incidence of adverse events. This retrospective study included 1,157 COVID-19 patients who were hospitalized in Huoshenshan Hospital from 12 March 2020 to 11 April 2020. Data on the patients’ demographic characteristics, initial symptoms, comorbidities and laboratory tests were collected. Totally, 571 (49.4%) female and 586 (50.6%) male COVID-19 patients were enrolled. The incidence of myocardial injury was higher among men than women (9.2% vs. 4.9%, p = 0.004). In the logistic regression analysis, age, and chronic kidney disease were associated with myocardial injury in both sexes. However, hypertension (odds ratio [OR]=2.25, 95% confidence interval [CI] 1.20-4.22), coronary artery disease (OR=2.46, 95% CI 1.14-5.34), leucocyte counts (OR=3.13, 95% CI 1.24-7.86), hs-CRP (OR=4.45, 95% CI 1.33-14.83) and D-dimer (OR=3.93 (1.27-12.19), 95% CI 1.27-12.19) were independent risk factors only in the men. The correlations of hs-CRP and D-dimer with hs-cTnI and BNP were stronger in the men. The incidence of myocardial injury in COVID-19 patients is sex-dependent, predominantly in association with a greater degree of inflammation and coagulation disorders in men. Our findings can be used to improve the quality of clinical management in such settings.